An appraisal of the need for infrared radiation protection in sunscreens. Issue 3 (5th February 2016) - Diffey, Brian; Cadars, Benoît
Abstract : Many sunscreens claim to protect against IR radiation. We review biological and clinical effects attributed to IR, as well as solar and industrial IR exposure levels and question whether IR protection in sunscreens is necessary. Abstract : Many sunscreens incorporate agents that are said to protect against infrared (IR) damage in the skin but we lack any real data on their benefit in the context of normal human behaviour in the sun. The object of this study was to examine typical IR exposure levels to the sun and industrial sources in order to decide whether there is a need for sunscreens to contain agents that protect against IR radiation, specifically the IR-A waveband. We reviewed claims currently made by products offering protection against IR-A and studies on the biological and clinical effects attributed to IR-A, and compared IR-A exposure levels from these studies with those typically received from the sun and from industrial sources. We found that annual levels of IR-A exposure resulting from typical behaviour in the sun are commensurate with those experienced occupationally by workers exposed to industrial sources of IR, such as steel and glass furnaces. Yet these workers appear to suffer little in the way of chronic skin damage. We conclude that there is not compelling evidence to demonstrate that observable, deleterious cutaneous effects are occurring at doses of solar IR radiation corresponding to those experienced by populations in their normal environments and for this reason we believe it is premature to incorporate IR protection into topical sunscreens and to make claims related to ageing of the skin that consumers may expect to see.